I wanna prove that $x+1 = 1+x$ (without considering "$x+0=x$",and Im using the old definition of Peano axioms)
This is my try:
Using this basis:

$(1):1+x = x^+$
$(2):x^+ +y=(x+y)^+$

Actually my idea is if numbers succesor are equal then actual numbers are equal too. (based on Peano axioms) $$(1+x)^+ = 1^+ + x = (1+1)+x$$
and $$(x+1)^+ = x^+ +1 = (1+x)+1$$
But I stucked in how to show that this two are equal.

Somebody help :)


We will prove by induction that $x+1=x^+$.

Basis: $1+1=1^+$, from (1).

Induction step: assume $x+1=x^+$ and prove that $x^++1=(x^+)^+$.

By (2): $x^++1 = (x+1)^+ = (x^+)^+$ using induction hypotheses and substitution for equality.

Having proved that $x+1=x^+$, for every $x$, we use (1) and transitivity and symmetry of equality to conclude that:


  • $\begingroup$ Thanks!Clear and easy to understand. $\endgroup$ – program_craft Feb 25 at 16:18
  • $\begingroup$ @program_craft - you are welcome :-) $\endgroup$ – Mauro ALLEGRANZA Feb 25 at 16:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.